The willingness and perceptions of Surinamese individuals in the Netherlands on living tissue donation: A qualitative and exploratory study - Charifa Zemouri; Assia Nait Kassi; Muriel Sinselmeijer; Bert Elbertse; Yvonne Mulder; Sara Jobse; Ilyaz Nasrullah; Jennifer Jubitane; Shelaika Hoogdorp; Eva-Maria Merz (PLoS ONE, 2025)
Background The Surinamese population in the Netherlands is an ethnically diverse group with a specific need for transfusion or transplantation due to a higher prevalence of diseases like beta-thalassaemia and sickle cell disease. This study explored the willingness of Surinamese individuals in the Netherlands to donate blood, stem cell, and live organ donation, and preferred information dissemination methods. Methods A sequential, qualitative, exploratory study was conducted using an online questionnaire and a focus group to examine the willingness to donate living tissue. Participants were Surinamese individuals aged 18–55 residing in the Netherlands. The questionnaires were inductively thematically analysed. The results led to in-depth questioning and discussion among the focus group, which consisted of four men and four women. The session was recorded and transcribed verbatim for thematic analysis. Results We identified ten themes across tissue types: 1) awareness of needs; 2) information and knowledge; 3) donation process; 4) cues to action; 5) attitude; 6) religion; 7) health challenges; 8) fear; 9) social cohesion and solidarity; 10) relationship with recipient. Willingness to donate blood was high, but they faced barriers, including registration challenges and limited access. Stem cell donation was seen as invasive. Living organ donation was considered only for emotionally close recipients. Participants were unaware of shortages and the importance of ethnic matching. They called for inclusive campaigns reflecting broader ethnic diversity, not just Suriname. Future strategies should simplify access to information, registration, and donation processes. Conclusion Most participants were unfamiliar with living donations, and perceived barriers were key reasons for not donating. Emotional bonds and awareness of ethnic matching and shortages motivated willingness. Participants stressed the need for tailored, ethnic-specific campaigns to address barriers and misconceptions, emphasise ethnic matching, and highlight reliance on their communities for successful living donation.